Photoelectron spectroscopy of ionic liquid-based interfaces - Lovelock, Kevin R.J.; Villar-Garcia, Ignacio J.; Maier, Florian; Steinrück, Hans-Peter; Licence, Peter (Chemical Reviews, 2010)
Photoelectron spectroscopies (PES) are a class of surface analysis techniques that involve irradiating the sample in Vacuo with photons and measuring the kinetic energy of the electrons emitted. Ultrahigh vacuum (UHV) is generally required to analyze the emitted photoelectrons without interference from gas phase collisions. XPS can be used to identify and quantify the different chemical environments of the same element within a given IL. Each individual element signal is a function of the chemical environment of the atoms of interest. There are two contributions to the observed chemical shifts in XP spectra, namely initial and final state effects. Initial state effects are those that affect the charge of the atom before the photon strikes and are described by calculations of the ground state of a particular system.